Biomechanical symmetry in elite rugby union players during dynamic tasks: an investigation using discrete and continuous data analysis techniques - Marshall, B.; Franklyn-Miller, A.; Moran, K.; King, E.; Richter, C.; Gore, S.; Strike, S.; Falvey, E. (BMC Sports Science, Medicine and Rehabilitation, 2015)
Background